IMPLEMENTASI PROGRAM PEMBANGUNAN DESA SEBAGAI PEMANFAATAN DANA DESA DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT (STUDI DI DESA LAILANGGA KECAMATAN WADAGA KABUPATEN MUNA BARAT) - Amin, Ali; Upe, Ambo; Juhaepa, Juhaepa (Universitas Halu Oleo, 2020)
This study aims to determine how the implementation of the village development program an as use of village funds in improving the welfare of the community in Lailangga village, Wadaga District West Muna Regency. The results of this research are disorganizing how to implement the village development program As the use of funds village in increasing the welfare of the community as seen from planning or village government work plan budgeting APBDesa, and the realization stage or the implementation of the Realization program is a necessity of the village community in accordance with village government deliberations with the community. Supporting factors implementation of the village development program as an use of village funds Good communication between the village government and the community is established good communication is the key to running a program effectively Resources are also very influential, including human resources, for example level of public education clear bureaucratic structure and attitudes or dispositions program implementers Inhibiting factors for program implementation Village development is a clash of interpretations of goals between the government with society and collisions.